2008
DOI: 10.1007/s00384-007-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of abdominal aortic aneurysm associated with colorectal cancer: presentation of 14 cases and literature review

Abstract: From the analysis of the literature and our experience, it is evident that, when AAA and CRC are coexistent with preoperative diagnosis of both diseases, single-stage intervention, when feasible for patient in general and local conditions, has to be preferred due to the lower morbidity. Single-stage treatment avoids a second surgical and anesthesiologic trauma and eliminates the risks joined with the non-treated lesion, increasing, however, the magnitude of the operation. Endovascular therapy, for its less inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The magnitude of the operation is increased, however. Veraldi et al reported lower morbidity and mortality in patients with CRC and AAA treated in one stage versus two stages (8 and 4.5% vs. 21.3 and 6%, respectively) [8]. Endovascular therapy appears suitable for a single-stage procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the operation is increased, however. Veraldi et al reported lower morbidity and mortality in patients with CRC and AAA treated in one stage versus two stages (8 and 4.5% vs. 21.3 and 6%, respectively) [8]. Endovascular therapy appears suitable for a single-stage procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The concomitant occurrence of aortic aneurysm and CRC appears to be increasing, from 0.5% to 2% [2] , as a result of the increase in the two individual diseases, which is caused by increased life expectancy and improved imaging capability in revealing additional asymptomatic disease [5] . Published studies are either small case series or limited retrospective reports [3,6] , therefore, the ideal treatment strategy represents a therapeutic dilemma [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Veraldi et al [5] have found, from Medline 1987-2005, a total of 229 cases of associated aortic aneurysm and CRC. Four emergency operations have been reported, one for rupture of the aortic aneurysm, two for unstable aneurysm, and one for diastatic rupture of the cecum by the stenosing neoplasm in the sigmoid colon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations